Well Log Sequence Stratigraphic and Palynological Analysis of Late Miocene to Pliocene Agbada Formation, Southwestern Niger Delta Basin, Nigeria - Adebayo, Olajide Femi (Review of Environment and Earth Sciences, 2014)
Sequence stratigraphic interpretation of Chev-1, 2, and 3 wells offshore western Niger delta basin was carried out based on the vertical relationship of the lithofacies associations, electronic well-log, palynologic and foraminiferal data and the existing stratigraphic framework of the Neogene succession in the Niger delta basin. Each well was analyzed in terms of the system tracts, maximum flooding surfaces and sequence boundaries. The recovered palynomorphs together with planktonic foraminifera suggest Late Miocene to Pliocene age. The palynological assemblages exhibit cyclic changes which are here related to the sedimentary evolution.Eighteen depositional sequences were recognized; there are five in Chev-1, ten in Chev-2 and seven in Chev-3. Three of those in Chev-1 and Chev-2 are correlatable while one is correlatable between Chev-2 and 3. These sequence stratigraphic data are matched with existing global standard biostratigraphic zonation scheme and global eustatic curve in order to allow a correlation of sequence beyond local and regional scales.